Evolution of plasticity-based wear damage in gross sliding fretting of a Ti-6Al-4V non-conforming contact - Mohd Tobi, A.L.; Sun, Wei; Shipway, P.H. (Elsevier, 2017)
This paper examines the evidence for a plasticity based wear mechanism in the fretting wear of Ti-6Al-4V. Driven by near-surface plastic strain accumulation, the generation of wear debris evolves from coarse metallic debris towards loose fine oxide debris generating W-shape wear scar. The overall wear effect however, is less pronounced at the later stages of wear due to a reduced propensity for plastic deformation in the contact associated with wear induced contact pressure reduction. The evidence suggests that the high wear rate at the early stages of a fretting test are due to debris = generation associated with gross plasticity whilst at the later stages, lower wear is associated with less plasticity accumulation.